2023
DOI: 10.1063/5.0161447
|View full text |Cite
|
Sign up to set email alerts
|

A laterally excited bulk acoustic resonator with scattering vias in electrodes

Zhiwei Wen,
Wenjuan Liu,
Tiancheng Luo
et al.

Abstract: Laterally excited bulk acoustic resonators (XBARs) using interdigital electrodes are currently limited in potential 5G applications due to the accompanied spurious modes and small capacitance. This Letter presents an XBAR with scattering vias in electrodes, named SV-BAR. The non-parallel boundaries thoroughly disrupt the coherent formation of standing waves in the lateral direction, thereby suppressing the higher-order spurious modes. The duty factor of SV-BAR is optimized as 0.5 using COMSOL Multiphysics fini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Remarkably, seminal work by Yang et al has demonstrated A1 mode resonators operating within the 5 GHz range, showcasing a K 2 e f f value of 29% [15], thereby highlighting their considerable potential in the sub-6 GHz domain. Nevertheless, a substantial challenge associated with A1 mode resonators is their vulnerability to spurious modes [16][17][18][19], which constitute a critical barrier to their extensive application. Consequently, the strategic goal of minimizing or eradicating these spurious modes becomes an essential consideration for the advancement of high-performance A1 mode resonators.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, seminal work by Yang et al has demonstrated A1 mode resonators operating within the 5 GHz range, showcasing a K 2 e f f value of 29% [15], thereby highlighting their considerable potential in the sub-6 GHz domain. Nevertheless, a substantial challenge associated with A1 mode resonators is their vulnerability to spurious modes [16][17][18][19], which constitute a critical barrier to their extensive application. Consequently, the strategic goal of minimizing or eradicating these spurious modes becomes an essential consideration for the advancement of high-performance A1 mode resonators.…”
Section: Introductionmentioning
confidence: 99%